Impact of official development assistance on sustainable development of Pakistan / Fouzia Perveen and Afaq Ali Khan - Perveen, Fouzia; Ali Khan, Afaq (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This research paper aims to find out the relationship between Official Development Assistance and sustainable development in Pakistan. Time series data was taken for the period of 42 years (1976 -2017). Sustainable Development is a dependent variable for which a proxy variable of Adjusted Net Savings has been deployed. ODA (% of GNI), Inflation, Per Capita GDP and Trade (GDP %) have been used as explanatory variables. Augmented Dickey-Fuller Test has been applied to examine the nature of the data as time series data may contain unit root problems. ADF test confirms mixed order of integration for the selected variables. Hence Autoregressive Distributed Lag (ARDL) Approach was applied to find out long-run relationship dynamics among the variables. Akaike info criterion (AIC) approach has been used to specify the optimal lag period. The F-Bounds test was significant at a 5% confidence level, showing the strong cointegration among variables, suggesting verification of short-run and long-run coefficients. Estimation of Error Correction Regression resulted in a significant long-run relationship between ODA and Sustainable Development. ECM Regression also signifies the negative and significant value of the speed of adjustment term, confirming that the model is stable and convergent towards the equilibrium. Overall results of this study demonstrate a positive and highly significant relationship between ODA and the measure of sustainable development in Pakistan.